Embedded Discounting - Daniel Møller Sneum; Emilie Rosenlund Soysal; Frikk Nesje; Mark C. Freeman (Center for Economic Studies and ifo Institute (CESifo), 2023)
The appraisal of public investments is subject to formal guidelines which often require input prices, such as forecasted energy prices. Using Danish guidelines as a case study, we explore the discounting assumptions in these input prices and find rates ranging from 2.97% to 17.5%, markedly different from the headline discount rate of 3.5%. This is not unique to Denmark and discrepancy in embedded discount rates can lead to false rejection of projects. We offer three possible explanations for such differences, based on positions on how the discount rate should be set.
Keywords: D61; H43; L51; Q48; 330; discounting; social discount rate; cost-benefit analysis; public guidelines